Women’s Candidacy in Local Level Elections, 2017 - Shrestha, Amrit Kumar; Phuyel, Shyam Prasad (Dristikon: A Multidisciplinary Journal, 2019)
Local levels have emerged as an epicenter of national politics. They influence the province and federal levels. Nepal has 753 local levels; among them 293 are municipalities and 460 are rural municipalities (RM). Women's candidacy in electoral politics is a key issue of political discourse. After the people's movement of 2006, Nepal has made several constitutional and legal reformations in regarding of inclusion of women in politics, particularly at local levels. This article focuses on women candidacy at the local level election of Nepal that held in 2017. It is based on data published by the Election Commission of Nepal. The election result indicates a positive change in terms of women's participation at the local level. Although most of the women are cast at the post of deputy mayor or vice-president of RM, 718 women are entertaining the executive post of the local level. This article analyzes women's participation as a candidate and elected candidate in various posts and positions of local level comparing to their counter partner men candidates.